2018
DOI: 10.3390/su10124753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Grazing Systems on Aboveground Biomass and Plant Species Dominance in Typical Chinese and Mongolian Steppes

Abstract: This study investigated the effects of different grazing systems on plant communities, and examined the causes of Mongolian grassland desertification. The typical steppes near the Chinese-Mongolian border were studied using quadrat sampling and remote sensing methods. Aboveground biomass in the steppe areas differed significantly among the three grazing systems (p < 0.05): Biomass in the grazing-prohibited areas (455.9 g) was greater than that in the rotational-grazing areas (268.4 g) and the continuous grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Based on SAR data, the HH/VV ratio related well to grassland phenology [136]. In semi-arid regions, the SAVI possibly improves the analysis of the grassland condition and use intensity [145,192] due to larger amounts of soil backscattering. Even though the current grassland condition might be well monitored by these indices, data gaps due to clouds are a problem, as for all optical satellite data products.…”
Section: Assessment Of the Used Remote Sensing Sensors And Indices Ofmentioning
confidence: 98%
“…Based on SAR data, the HH/VV ratio related well to grassland phenology [136]. In semi-arid regions, the SAVI possibly improves the analysis of the grassland condition and use intensity [145,192] due to larger amounts of soil backscattering. Even though the current grassland condition might be well monitored by these indices, data gaps due to clouds are a problem, as for all optical satellite data products.…”
Section: Assessment Of the Used Remote Sensing Sensors And Indices Ofmentioning
confidence: 98%
“…There are other factors, including those human-related practices listed in Table 5, which might be similarly important and preferably included in the driving factor analysis. For example, rotating grazing, as a management practice recommended for improving vegetation productivity [46], was not indicated in the variable of grazing intensity and thus not reflected in the explained variance, although grazing rotationally or not could mean a significant difference on the impact of RCU. Moreover, while the included human-related factors, RCU, and their relationships were found to vary among administrative units, the analysis of the driving forces for RCU at the county level may generalize the effect between the selected variables and RCU.…”
Section: Driving Factors For Reduced Carbon Uptake (Rcu)mentioning
confidence: 99%
“…Taking grazing management as an example, the exclusion or restriction of grazing resulted in a significant improvement in vegetation density in Horqin sandy land located in the southeast of IMAR [45]. Rotational or nomadic grazing also helps reduce the negative impact on grassland vegetation [46]. Thus, fenced grazing (exclusion of grazing) and rotational grazing can be adopted as OGMPs for the S-T-V patches in those study regions.…”
Section: Optimal Grassland Management Practices (Ogmps)mentioning
confidence: 99%
“…The impacts of livestock grazing on the ecosystems were associated in previous studies with canopy cover, the response of the dominant plant species to grazing, different grazing regimes, and site history (Chen et al, 2014;Gan et al, 2012;K'Otuto et al, 2013;Kairis et al, 2015;Lecain et al, 2000;Räsänen et al, 2017;Tagesson et al, 2015;Talore et al, 2016;Wagle et al, 2019;Yan et al, 2017). In a study conducted in Chinese and Mongolian steppes, Na et al (2018) showed that continuous grazing leads to reduction in aboveground biomass (AGB). Ma et al (2019) found a strong correlation between grazing intensity and vegetation indexes (AGB and NDVI).…”
Section: Impacts Of Lenient Temporary Vs Continuous Heavy Livestock Grazingmentioning
confidence: 99%